Negotiating democracy with authoritarian regimes. EU democracy promotion in North Africa. Issue 5 (4th July 2019) - van Hüllen, Vera
ABSTRACT: In order to better understand the dynamics of international cooperation on democracy promotion with authoritarian regimes, this article looks into the processes and results of negotiations on democracy (promotion) between the European Union (EU) and two of its North African neighbours (Morocco, Tunisia) in the decade leading up to the Arab uprisings. Asking if, how, and to what effect the EU and its Mediterranean partners have negotiated issues related to democracy promotion, it analyses official documents issued on the occasion of their respective association council meetings in 2000-2010. It shows that partners have indeed addressed these issues since the early 2000s, however, without engaging in substantive exchanges. Most of the time, conflicts have been neither directly addressed nor resolved. Where there are traces of actual negotiations leading to an agreement, these are clearly based on a logic of bargaining rather than arguing. These findings challenge the picture of harmony and cooperation between the EU and Morocco. Furthermore, they point to the low quality of these exchanges which reinforces the dilemma of international democracy promotion in cooperation with authoritarian regimes.